Characterization of Virulence Factors and Two-Component Regulatory System Genes in Uropathogenic Escherichia coli Isolates from Young Women with Urinary Tract Infections - Al-Daraji, Ali H.; Flayyih, May T. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Urinary tract infections are one of the most common bacterial infections, caused mainly by Escherichia coli. Uropathogenic Escherichia coli (UPEC) possess virulence factors that can worsen infections, partly regulated by the BarA/UvrY two-component system, which controls genes associated with adhesion, motility, and biofilm formation through small RNAs and carbon metabolism regulators. Objectives: To determine the pathogenicity and some genotype features of Escherichia coli from urine specimens collected from young women patients and assess their antibiotic resistance. Methods: Between September and November 2024, 200 urine samples were collected from young women aged 18 to 30 who had urinary tract infections, from a number of major hospitals in Baghdad. Identification of bacteria was confirmed using differential and chromogenic media, followed by biochemical confirmation with the VITEK 2 Compact System. Antimicrobial susceptibility was tested using the VITEK 2 Compact System. The ability of Escherichia coli to form biofilm, swarm, and produce hemolysin was evaluated. Conventional PCR methods were used to detect the prevalence of the two-component system genes in Escherichia coli. Results: The isolation rate of Escherichia coli from urine samples was 44.5%, yielding 89 isolates. High resistance to cefotaxime (82.5%) was observed, while all isolates were fully sensitive to meropenem, amikacin, and tigecycline. A substantial 85% of isolates produced β-lactamase, and 2.5% displayed both β-lactamase production and polypeptide resistance mechanisms. Production of hemolysin was seen in 48.3% of isolates, while 34.8% showed swarming motility. Biofilm formation varied, with 13.4% being moderate producers, 29% being weak producers, and 57.3% not producing. Genotypic analysis of 16 representative isolates revealed the presence of the BarA and UvrY genes. Conclusion: This study highlighted the critical role of UPEC in urinary tract infections among young women, marked by significant cefotaxime resistance. Despite the uniform presence of the BarA and UvrY genes, isolates displayed diverse virulence profiles, underscoring the complex interplay between resistance and pathogenicity.